EFFECT OF NIGELLA SATIVA OIL ON BLOOD PRESSURE IN ADULTS WITH HYPERTENSION IN KENDARI INDONESIA - Ananda, Siti Hadrayanti; Narmawan, Narmawan (Public Health of Indonesia, 2020)
Background: Hypertension remains a big challenge for people in Indonesia, especially in adults. Therefore, an effort to reduce high blood pressure is needed. Nigella sativa or known as habbatussauda is one of herbs that is assumed to be able to reduce high blood pressure.Objective: This study aims to determine the effect of nigella sativa oil on blood pressure in hypertensive adults.Method: A quasi-experimental research design with pretest-posttest with control group design. A total of 60 respondents were selected using simple random sampling technique, which 30 were randomly assigned in an intervention and a control group. Nigella sativa oil was given every day for three months. Data were analyzed using descriptive statistics and ANOVA.Results: There was a significant effect of nigella sativa oil on changes in systolic and diastolic blood pressure (p<0.001).Conclusion: Nigella sativa oil is significantly reducing blood pressure among adults with hypertension. Therefore, nigella sativa oil can be used as an alternative therapy for hypertension.